Relationship between Self-care Behaviors and Inherent Dignity and their Predictors in the Elderly with Chronic Heart Failure - Brojerdi, Mahbobeh; Rahmani-Anaraky, Hossein; KolagariKolagari, Shohreh (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Self-care is one of the most important strategies to control heart failure that can increase patients’ independence and satisfaction and maintain their respect and dignity in the family and society. The present study aimed to investigate the relationship between self-care behaviors and inherent dignity and their predictors in the elderly with chronic heart failure (CHF). Methodology: A cross-sectional study was conducted on 109 elderlies visiting the cardiology clinics affiliated with the Golestan University of Medical Sciences in 2019. The participants were selected based on convenience sampling and the data were collected using a clinical and demographic information form, inherent dignity Questionnaire (IDQ), and the European Heart Failure Self-Care Behavior Scale (EHFSCBS). The obtained data were statistically analyzed in SPSS-16 by using descriptive statistics (mean, standard deviation, relative frequency, and absolute frequency) and inferential statistics (univariate and multiple linear regression, the independent t-test, the Mann–Whitney U test, one-way ANOVA, and the Kruskal-Wallis test) at the 0.05 level of significance. intrinsiv Results: The mean score of self-care behaviors and inherent dignity was equal to 22.42±2.52 and 121.44±9.89, respectively. The results showed that there was a poorand insignificant correlation between self-care behaviors and inherent dignity (r=0.07, p=0.42). Among the predictors of self-care behaviors in the elderly with CHF, age in both regression models and educational attainment in the univariate linear regression modelwere statistically significant and thus were identified as the predictors of self-care behaviors in such patients. Conclusions: Although the mean scores of self-care behaviors and inherent dignity were evaluated good, there was a poor and insignificant relationship between these two variables. In addition, variables such as age, ethnicity, insurance coverage, and educational attainment were identified as the predictors of self-care behaviors and inherent dignity in such patients.